Direct oral anticoagulants compared to low‐molecular‐weight heparin for the treatment of cancer‐associated thrombosis: Updated systematic review and meta‐analysis of randomized controlled trials. Issue 4 (21st May 2020) - Moik, Florian; Posch, Florian; Zielinski, Christoph; Pabinger, Ingrid; Ay, Cihan
Abstract: Background: Low‐molecular‐weight‐heparins (LMWHs) have been established for the treatment of cancer‐associated venous thromboembolism (VTE). Recently published randomized controlled trials (RCTs) have compared direct oral anticoagulants (DOACs) with LMWHs. The aim of this systematic review and meta‐analysis was to evaluate efficacy and safety of DOACs versus LMWHs and update the evidence for treatment of VTE in cancer. Methods: Biomedical databases were screened for RCTs evaluating DOACs for cancer‐associated VTE. Primary efficacy and safety outcomes of this meta‐analysis were recurrent VTE and major bleeding at 6 months. Secondary outcomes comprised clinically relevant nonmajor bleeding (CRNMB), major gastrointestinal (GI) and genitourinary bleeding, mortality, fatal bleeding/pulmonary embolism, and treatment discontinuation rate. We performed prespecified subgroup analyses. Pooled relative risk (RR) and 95% confidence intervals (CIs) were obtained by the Mantel‐Haenszel method within a random‐effect model. Results: We screened 759 articles and included 4 RCTs (n = 2894). DOACs significantly reduced recurrent VTEs compared to LMWHs (5.2% vs 8.2%; RR, 0.62 [95% CI, 0.43‐0.91]), but were associated with a nonsignificant increase in major bleedings (4.3% vs 3.3%; RR, 1.31 [95% CI, 0.83‐2.08]) and a significant increase in CRNMB (10.4% vs 6.4%; RR, 1.65 [95% CI, 1.19‐2.28]). Mortality risks were comparable between groups (RR, 0.99 [95% CI, 0.83‐1.18]). Preterm treatment discontinuation was less common with DOACs (RR, 0.88 [95% CI, 0.81‐0.96]). Major bleeding was more frequent in patients with GI cancer treated with DOACs (RR, 2.30 [95% CI, 1.08‐4.88]). Conclusion: In patients with cancer‐associated VTE, DOACs are more effective in preventing recurrent VTE compared to LMWH. However, risk of bleeding is increased with DOACs, especially in patients with GI cancer.